Self-Assembled Multilayer Single-Walled Carbon Nanotube Thin Film Transistors and Doping Regulation - Xiangxiang Gao; Zhenhua Lin; Jincheng Zhang; Yue Hao; Jingjing Chang (IEEE Journal of the Electron Devices Society)
Semiconducting single-walled carbon nanotubes (SWCNTs) have stimulated tremendous research interest in high performance electronics thanks to their impressive mechanical and electronic properties. However, it is still challenging to prepare wafer-scale SWCNTs thin films and fine-tunable device performance. Here, layer-by-layer (LbL) assembly is presented as an effective approach to prepare multilayer SWCNT thin films by coordinating poly(diallyldimethylammonium chloride) (PDDA) with SWCNTs. The thickness of SWCNTs thin film is linearly dependent on the bilayer numbers. Thin film transistors (TFTs) fabricated from SWCNTs thin films showed prominent device performance with a mobility of $\rm 15.3 cm_{2} · V_{1}· s_{1}$ . Further the molecular dopants bis (trifluoromethane) sulfonimide (TFSI), with strong electro-withdrawing capability and protonating nature, was utilized to functionalize SWCNTs thin films, thereby regulating their electronic performances. The TFSI surface functionalization can remove excess electrons from SWCNT thin films, resulting in improved on-state current, increased carrier mobility and positively shifted threshold voltage. The molecular doping holds great promise for the future realization of large-area, low-power logic circuits and high-performance electronics.